Overview of chicken embryo genes related to sex differentiation - Xiaolu Luo; Jiancheng Guo; Jiahang Zhang; Zheng Ma; Hua Li (PeerJ, 2024)
Sex determination in chickens at an early embryonic stage has been a longstanding challenge in poultry production due to the unique ZZ:ZW sex chromosome system and various influencing factors. This review has summarized the genes related to the sex differentiation of chicken early embryos (mainly Dmrt1, Sox9, Amh, Cyp19a1, Foxl2, Tle4z1, Jun, Hintw, Ube2i, Spin1z, Hmgcs1, Foxd1, Tox3, Ddx4, cHemgn and Serpinb11 in this article), and has found that these contributions enhance our understanding of the genetic basis of sex determination in chickens, while identifying potential gene targets for future research. This knowledge may inform and guide the development of sex screening technologies for hatching eggs and support advancements in gene-editing approaches for chicken embryos. Moreover, these insights offer hope for enhancing animal welfare and promoting conservation efforts in poultry production.